2017
DOI: 10.1177/0363546516686057
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral Ligament Reconstruction Is Associated With Significantly Reduced ACL Graft Rupture Rates at a Minimum Follow-up of 2 Years: A Prospective Comparative Study of 502 Patients From the SANTI Study Group

Abstract: In a high-risk population of young patients participating in pivoting sports, the rate of graft failure with HT+ALL grafts was 2.5 times less than with B-PT-B grafts and 3.1 times less than with 4HT grafts. The HT+ALL graft is also associated with greater odds of returning to preinjury levels of sport when compared with the 4HT graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
437
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(479 citation statements)
references
References 48 publications
22
437
3
9
Order By: Relevance
“…They demonstrated that a combined reconstruction can be effective in controlling both rotational instability and anteroposterior laxity, without causing rigidity or limiting the joint range. Subsequently, these same authors (Sonnery‐Cottet et al, ) demonstrated that a combined hamstring tendon graft with ALL reconstruction entails a lower rate of graft failure than bone–patellar tendon–bone or quadrupled hamstring tendon graft in a high‐risk population of young patients who participated in pivotal sports. They assumed that a combined ALL–ACL reconstruction is also associated with a higher probability of returning to preinjury levels of the sport than the quadrupled hamstring tendon graft.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that a combined reconstruction can be effective in controlling both rotational instability and anteroposterior laxity, without causing rigidity or limiting the joint range. Subsequently, these same authors (Sonnery‐Cottet et al, ) demonstrated that a combined hamstring tendon graft with ALL reconstruction entails a lower rate of graft failure than bone–patellar tendon–bone or quadrupled hamstring tendon graft in a high‐risk population of young patients who participated in pivotal sports. They assumed that a combined ALL–ACL reconstruction is also associated with a higher probability of returning to preinjury levels of the sport than the quadrupled hamstring tendon graft.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on anterolateral stabilization in adults has been reported with favorable outcomes. Sonnery-Cottet et al 10 compared the graft rupture rate in 3 ACLR groups: 4-strand hamstring tendon (HT), boneepatellar tendonebone (BPTB), and HT þ ALL. The combined HT and ALL graft group experienced 2.5 and 3.1 times less graft rupture compared with BPTB and 4HT, respectively at minimum 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The combined HT and ALL graft group experienced 2.5 and 3.1 times less graft rupture compared with BPTB and 4HT, respectively at minimum 2-year follow-up. 10 Marcacci et al 11 reported a 10-to 13-year follow-up on 54 patients who underwent ACLR with a similar technique. After 11 years, only 2 patients had >5 mm manual maximum side-to-side difference in laxity based on the KT-2000 arthrometer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluated other criteria for a combined procedure with respect to the grade of the preoperative pivot-shift test, 16 revision ACL reconstruction cases, or patient age and sporting activity level. 17 The results of the study of Ibrahim et al 16 indicated improvements for the subjective and objective outcomes for a combined ACL and ALL reconstruction in patients with an unilateral ACL injury and high-grade pivot shift. But significant superior results of the combined procedure over the isolated ACL reconstruction were found only for the instrumented knee laxity testing.…”
mentioning
confidence: 97%
“…But significant superior results of the combined procedure over the isolated ACL reconstruction were found only for the instrumented knee laxity testing. Sonnery-Cottet et al 17 reported a lower rate of graft failure with combined ACL (using a hamstring tendon graft) and ALL reconstruction compared with an isolated ACL reconstruction (using quadrupled hamstring graft or bone-patellar tendon-bone graft) after a mean followup of 38.4 months in a cohort of young patients participating in pivoting sports. The most recent study of Rosenstiel et al 18 showed excellent outcomes for combined ACL and ALL reconstructions in professional athletes with respect to graft rupture rates, return to sport, knee stability, and reoperation rates after injury.…”
mentioning
confidence: 99%